Leveraging governance strategies adopted by health facility governing committees in response to COVID-19 outbreak at the local level in Tanzania: A qualitative study - Anosisye Mwandulusya Kesale; Eliza Mwkasangula; Mikidadi Muhanga; Christopher Mahonge (Public Library of Science (PLoS), 2022)
The governance of epidemics is very critical for curbing and responding to several infectious epidemics. This study was conducted to explore the experience of the Health Facility Governing Committees (HFGCs) on the governance strategies they adopted to levarage the COVID 19 epidemic in their primary health facilities in Tanzania. An exploratory qualitative design was employed to study the governance strategies adopted by HFGCs during the COVID19. In this study, fourteen (14) HFGC chairpersons and ninety one (91) HFGC members with experience regulating primary health centers during a COVID 19 pandemic were involved. The study included four (4) governance response metrics that were discovered to be commonly used by HFGCs. These included coordinating responders, providing health information, explaining health hazards, and conducting out health interventions. Despite variations in implementation strategies, only two (2) governance response measures, coordinating responders and implementing, were found to be consistently applied by the majority of HFGCs. The nature of the governance path chosen by the Tanzanian government has been found to have influenced the slow reaction of primary health care governance actors such as HFGCs. Despite being empowered by Direct Health Facility Financing, COVID 19 presented challenges to several HFGCs. Though observed to be autonomous and expected to make judgments based on their circumstances, higher-level governance actors' opinions and actions on epidemics influenced the practices of local-level governance actors, including HFGCs. Indeed, for the HFGCs' potential to be realized, they must be empowered in ways other than fiscal and political decentralization. Other aspects of empowering governance actors, such as capacity building and education level, should be considered in order for them to completely realize their potential.